Experiences of undetectable = untransmittable among couples with different HIV serostatus: a qualitative study in Tanzania and Uganda - Elizabeth Senkoro; Timothy Muwonge; Leila Samson; Vicent Kasiita; Alisaati Nalumansi; Brenda Kamusiime; Gertrude Mollel; Maja Weisser; Andrew Mujugira (BMC Public Health)
Abstract Background HIV serodifferent couples where one partner is living with HIV and the other is not, remain a key population for HIV prevention. Maintaining an undetectable viral load eliminates the risk of sexual HIV transmission, this principle is often summarised as undetectable = untransmittable (U = U). However, the extent to which this principle is understood and utilised by serodifferent couples remains unclear. This study aimed to explore both partners’ perceptions, experiences and adoption of U = U within their relationships. Methods We conducted an exploratory qualitative study using in-depth interviews with 20 serodifferent couples (40 participants) between July and August 2023 in Ifakara, Tanzania and Kasangati, Uganda. Each partner was interviewed separately. Interviews explored: (1) Awareness of U = U, (2) Lived experiences related to U = U, and (3) Social perceptions of U = U and HIV serodifference. The interviews were audio-recorded, transcribed, and analysed using thematic analysis with Atlas.ti for coding. Results All participants were in a heterosexual serodifferent relationship and had mutually disclosed their status. The average age was 25 years, and couples had been partnered for approximately 3.5 years. All 40 participants (100%) had basic knowledge of U = U or treatment as prevention. The qualitative analysis identified four key themes that were broadly consistent in both settings: (1) Knowledge of U = U facilitated adoption, with initial doubts giving way to trust over time as partners remained HIV-negative; (2) Disclosure triggered emotional responses, which were alleviated through counselling, with U = U influencing relationship confidence and fertility decisions; (3) Use of additional prevention (PrEP, condoms) reinforced trust in U = U, addressing residual concerns about adherence and fidelity; (4) Persistent stigma and limited community awareness constrained U = U’s potential impact. Themes were largely consistent across Uganda and Tanzania, though Ugandan participants more frequently reported detailed provider counselling and PrEP use. Conclusion This study highlights how understanding experiences of U = U among HIV serodifferent couples in Tanzania and Uganda are shaped by personal, relational, and contextual factors. Our findings suggest that U = U communication strategies should be strengthened through context-specific counselling, improved access to viral load testing, and community education. Further research is needed to explore how U = U is perceived and adopted in more diverse settings.